A Case Study on Huawei Technologies - Maria Del Mar Chacon; Abhishek Rajawat (Journal of The Community Development in Asia, 2019)
Huawei Technologies Co., Ltd. is a Chinese company. Nowadays, Huawei is becoming a very recognized company worldwide, due to its high technological quality products and innovation. These Chinese company is leading global provider of information and communications technology infrastructure and smart devices. With integrated solutions across four key domains, telecom networks, IT, smart devices, and cloud services. Huawei is committed to bring digital to every person, home and organization for a fully connected, intelligent world. Our proposal is to analyze the international strategies that Huawei have been applying to their success, what makes this company different from competition? Why clients or customers would prefer Huawei instead of other technological and recognized companies? and what can they improve in order to acquire more clients and work further to get into new markets and potentialized their products as the best ones. A profound study is done on how Huawei Technologies had made strategic choices to when and how to enter in an existing and highly competitive market. Also, the study explores the important canvases of their business model, which includes the precise time of entry, market segmentation and pricing strategy